2017
DOI: 10.1108/jamr-03-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Core software product management activities

Abstract: Purpose Software product management (SPM) unites disciplines related to product strategy, planning, development, and release. There are many organizational activities addressing technical, social, and market issues when releasing a software product. Owing to the high number of activities involved, SPM remains a complex discipline to adopt. The purpose of this paper is to understand what are the core and supporting SPM activities. Design/methodology/approach The authors adopted the research method of meta-eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
4
1
1
Order By: Relevance
“…4). These OrdEval results might be surprising since Requirements acquisition is considered one of the basic building blocks of the software development (Kruchten 2009;Maglyas et al 2017) with high importance to software project success (Fernandez et al 2017). The results can be explained by the fact that recently many new requirement acquisition techniques and approaches have been developed (Ernst et al 2014;Lauesen & Kuhail 2012;Lucassen et al 2016;Raspotnig & Opdahl 2013) and are probably perceived as innovations by the CIOs of the studied enterprises.…”
Section: Project Managementmentioning
confidence: 97%
“…4). These OrdEval results might be surprising since Requirements acquisition is considered one of the basic building blocks of the software development (Kruchten 2009;Maglyas et al 2017) with high importance to software project success (Fernandez et al 2017). The results can be explained by the fact that recently many new requirement acquisition techniques and approaches have been developed (Ernst et al 2014;Lauesen & Kuhail 2012;Lucassen et al 2016;Raspotnig & Opdahl 2013) and are probably perceived as innovations by the CIOs of the studied enterprises.…”
Section: Project Managementmentioning
confidence: 97%
“…Product manager is a role uniting technical and business perspectives in developing software products to provide value to the customer [9]. Product management has been existing since its adoption at Procter &Gamble in the 1930s [17] but did not become popular in software organizations until the late 1990s (aka software product management) [7].…”
Section: The Product Manager Rolementioning
confidence: 99%
“…PMs participate in strategic management, are responsible for product strategy and product planning, and orchestrate development, market, sales, distribution, and service and support. Based on this framework, Maglyas et al [9] identified 12 activities that product managers are engaged in practice, where vision creation, product lifecycle management, roadmapping, release planning, and product requirements engineering are described as core activities (see Table 1 for the definitions). In addition to the core activities, the authors describe other activities that the product manager may be involved in but that can, in practice be delegated to other functions.…”
Section: The Product Manager Rolementioning
confidence: 99%
See 1 more Smart Citation
“…e planejamento (ciclo de vida, engenharia de requisitos, etc.) do produto de software [Ebert et al, 2014;Fricker, 2012;Maglyas et al, 2017]. A estratégia visa: especificar o valor entregue pelo produto de software em consonância com o modelo de negócios da organização, direcionar a evolução do produto de software em alinhamento com a estratégia da organização e especificar os requisitos e restrições de negócio (perspectiva interna da organização) e mercado (perspectiva externa à organização) que devem ser considerados no processo de software.…”
Section: Introductionunclassified